Equity, Welfare, and the Setting of Trade Policy in General Equilibrium - Francois, Joseph; Rojas-Romagosa, Hugo (World Bank, Washington, DC, 2012)
The authors analyze general equilibrium relationships between trade policy and the household distribution of income, decomposing social welfare into real income level and variance components and emphasizing Gini and Atkinson indexes. They embed these inequality-adjusted social welfare functions in a general equilibrium structure mapping from tariff protection to household inequality. This yields predictions regarding the linkages between trade protection, country characteristics, and inequality within a broad general equilibrium framework. In addition, the authors can separate the efficiency and equity effects of tariffs on welfare. They then examine endogenous tariff formation when policymakers care about both equity and special interests.